Reflections of patient and public involvement from a commissioned research project evaluating a nationally implemented NHS programme focused on diabetes prevention - Rhiannon E. Hawkes; Caroline Sanders; Claudia Soiland-Reyes; Lisa Brunton; Kelly Howells; Sarah Cotterill; Carole Bennett; Eric Lowndes; Manoj Mistry; Helen Wallworth; Peter Bower (Research Involvement and Engagement, 2023)
Abstract Patient and Public Involvement and Engagement (PPIE) in research is recognised by the National Institute for Health and Care Research as crucial for high quality research with practical benefit for patients and carers. Patient and public contributors can provide both personal knowledge and lived experiences which complement the perspectives of the academic research team. Nevertheless, effective PPIE must be tailored to the nature of the research, such as the size and scope of the research, whether it is researcher-led or independently commissioned, and whether the research aims to design an intervention or evaluate it. For example, commissioned research evaluations have potential limits on how PPIE can feed into the design of the research and the intervention. Such constraints may require re-orientation of PPIE input to other functions, such as supporting wider engagement and dissemination. In this commentary, we use the ‘Guidance for Reporting Involvement of Patients and the Public’ (GRIPP2) short form to share our own experiences of facilitating PPIE for a large, commissioned research project evaluating the National Health Service Diabetes Prevention Programme; a behavioural intervention for adults in England who are at high risk of developing type 2 diabetes. The programme was already widely implemented in routine practice when the research project and PPIE group were established. This commentary provides us with a unique opportunity to reflect on experiences of being part of a PPIE group in the context of a longer-term evaluation of a national programme, where the scope for involvement in the intervention design was more constrained, compared to PPIE within researcher-led intervention programmes. We reflect on PPIE in the design, analysis and dissemination of the research, including lessons learned for future PPIE work in large-scale commissioned evaluations of national programmes. Important considerations for this type of PPIE work include: ensuring the role of public contributors is clarified from the outset, the complexities of facilitating PPIE over longer project timeframes, and providing adequate support to public contributors and facilitators (including training, resources and flexible timelines) to ensure an inclusive and considerate approach. These findings can inform future PPIE plans for stakeholders involved in commissioned research.